Despite large choice of effective therapies: Individuals with psoriasis still seem undertreated - Pilz, Anna Caroline; Zink, Alexander; Schielein, Maximilian C.; Hell, Katharina; Romer, Katrin; Hillmann, Elena; Baumer, Daniel; Reinhardt, Maximilian; Wagner, Nicola (Journal der Deutschen Dermatologischen Gesellschaft, 2021)
Background and objectives Due to the development of new anti-psoriatic drugs in combination with improved structures for implementation throughout Germany, the medical care of psoriasis patients has markedly improved. In this study we investigated the real-life utilization of the health care system and identified reasons for dissatisfaction in affected individuals.
CRIS-Team WoS Importer:2021-05-21